Animal Pox Viral Vaccines - Bhanuprakash, V.; Venkatesan, G.; Hosamani, M. (Indian Farming, 2015)
There is a potential in exploration of capripox viruses in generating multivalent vector vaccines as evident from many recombinant products based on poxvirus vectors. Vaccines against both sheeppox and goatpox are used for control of disease making it difficult to assess the current disease status in the small ruminants. In view of this, development of tools to differentiate infection from vaccination (DIVA) would be vital and such diagnostics would also be useful during post eradication phase of any disease when application of live vaccine would be ceased. The feasibility of application of combined vaccines like goatpox, PPR and orf needs to be explored to economize the costs incurred on the logistics in vaccination campaigns.